THE IMPORTANCE OF ETHICAL AND MORAL EDUCATION IN PREPARING YOUNG GIRLS FOR FAMILY LIFE - Vakhobova Nasibakhon Abdulhamidovna (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2024)
It is emphasized how important it is for girls to be prepared for family life by the upbringing they receive in their families and in various aspects of social life, as well as the importance of preparing girls for family life, emphasizing qualities such as honesty, humility, kindness, love, hard work, and the ability to maintain family harmony. It is also highlighted the need to instill a dislike for traits such as lying, laziness, selfishness, betrayal.